In situ studies of growth of carbon nanotubes on a local metal microheater. (18th November 2015) - Nerushev, O A; Ek-Weis, J; Campbell, E E B
Abstract: Using electron microscopy and in situ Raman spectroscopy we investigate carbon nanotube growth from ethylene on iron catalyst islands patterned on top of Mo electrodes, using a highly localized resistive on-chip-heating technique. A clear transition is observed between multi-walled and single-walled nanotube growth as the local temperature of the heater is increased. This can be rationalized in terms of the balance between incoming carbon flux and diffusion through the catalyst particle. The observed changes in heater performance on exposure to the hydrocarbon gas are explored and related to the formation of molybdenum carbide, leading to a rapid change in resistivity and heating power that increases the local temperature of the heater by up to 100 °C. This provides optimum conditions for nanotube growth after an incubation time that depends on the carbon flux.